Empowering Youth through Student-Led Anti-Drug Education in Collaboration with BNN - Satria Rahmat Akmal; Grasella Valentin; Nisrina Bunga Sarifah; Fawzan Ash Shiddiq; Oktavia Ramadhani; M Riadi Prabowo; M Nawal Adzim; Stefanus Alfares; Saut Ferdi; Muhammad Harri; Muhammad Kausar Maulana; Rachmaniar Myrianda Dwiputri (PT. Berkah Digital Teknologi, 2026)
This community service activity aims to analyze the role of university students participating in the Community Service Program (Kuliah Kerja Nyata/KKN) in the implementation of anti-drug counseling in collaboration with the National Narcotics Agency among youth. The program was conducted as a case study at SMK Yadika 6, focusing on strengthening students’ awareness and understanding of the dangers of drug abuse. The activity employed a participatory community development approach combined with community education methods, emphasizing active involvement of students, teachers, KKN students, and BNN representatives. The implementation stages consisted of planning, preparation, implementation, and evaluation. Data were collected through direct observation, short interviews with teachers and students, and documentation of activities. The results indicate that the collaboration between KKN students, schools, and BNN plays a significant role in enhancing the effectiveness of anti-drug education. KKN students acted as facilitators who delivered educational content in a more interactive and relatable manner, while BNN provided authoritative and credible information regarding the risks and consequences of drug abuse. Interview findings also revealed that family background and peer influence are major factors contributing to adolescents’ vulnerability to drug abuse, highlighting the importance of school-based preventive interventions. In conclusion, this community service program demonstrates that student-led initiatives supported by institutional collaboration can effectively strengthen drug abuse prevention efforts among youth. Sustainable partnerships between universities, schools, and government agencies are essential to creating a comprehensive and preventive anti-drug education strategy.